Design Learning Media of Traditional Game Quartet Card for Elementary School History Figures in the Resistance to the Netherland - S, Fadhila Ikrima; Sapriya; Sundari, Nina; Umar (International Conference on Elementary Education, 2022)
Elementary school students who are now in globalization era tend to forget the traditional game that is a legacy of ancestors since ancient times, then the limitations of teachers in making learning media in the social science, especially the history of the figures in the resistance to the Netherland be a background on this research. Based on this problem, the purpose of this research is to designing traditional game quartet card of learning media with Design & Development (D&D) method, type Hannafin & Peck to make learning media that can use to learning while playing by Students. The results on this research is valid based material expert validation results with achievement qualification is â€œVery Decentâ€ and then media expert validation results achievement with qualification â€œVery Decentâ€. Student responses to this learning media achievement level with qualification â€œVery Decentâ€. The teacher response to this this learning media achievement level with qualification â€œVery Decentâ€.